Fostering Emotional Well-being in Online Classrooms: Affective Learning Strategies in the Age of Digital Education - Novinda Grezen Nufninu; Maria Bere; Victoria Bria (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The rapid digitalization of education during the pandemic has brought new challenges and opportunities for student well-being. This study explores how affective-based learning strategies can support students’ emotional health in digital learning environments. Using a qualitative phenomenological approach, the research involved in-depth interviews, online classroom observations, and analysis of digital documents such as teaching materials and learning platform communications. The participants were teachers and students from secondary and higher education who had experience with affective learning practices, including mindfulness sessions, emotional reflection, and informal discussion forums. Thematic analysis revealed three key findings: first, students felt acknowledged and emotionally supported when given space to share their feelings; second, the integration of mindfulness practices, such as breathing exercises, helped reduce digital stress and improve focus; and third, digital empathy manifested through emojis, encouraging messages, and informal peer interactions played a critical role in maintaining emotional connection. However, challenges such as digital inequality and screen fatigue were also identified. This study contributes theoretically by reinforcing the role of emotional presence in digital pedagogy and practically by offering actionable strategies for educators to design well-being-oriented learning. The findings affirm that affective strategies are not supplementary but essential to sustaining mental health in online education. Limitations include the small sample size and limited observation of non-verbal cues. Future research is recommended to expand on these insights through longitudinal and mixed-method approaches.